دور الجامعة الإسلامية بالمدينة الم نورة وأكاديمية تعلم العربية في تنمية اللغة العربية في معهد ابن حجر الإسلامي : دراسة تقويمية في ضور المهارات اللغوية - Erliana , Leni; Mubarok, Alfian; Siddiq, Sayyid Munadi (STAINI Press, 2026)
Islamic educational institutions in schools and institutes face various challenges in teaching the Arabic language. Several institutes have made efforts to establish an Arabic language environment, and among the institutes that pay strong attention to Arabic language development is Ibnu Hajar Islamic Institute. This study aims to examine the role of the Islamic University of Madinah and the Taʿallum al-ʿArabiyyah Academy in developing Arabic language proficiency at Ibnu Hajar Islamic Institute in Indonesia through the implementation of an intensive language skills program held in August 2025 at the institute. The study employs a descriptive-analytical method by analyzing official educational programs, training courses, activities, and interviews. The findings indicate that the Islamic University of Madinah and the Taʿallum al-ʿArabiyyah Academy made significant contributions to the professional development of teachers at Ibnu Hajar Islamic Institute and to the enhancement of Arabic language teaching methods, including the direct method, the grammar–translation method, the audio-visual method, and the communicative approach integrating its three core components. The study also identifies several challenges faced by the institute, such as students’ weak linguistic background, the incomplete establishment of a fully Arabic language environment, low student motivation in learning Arabic, and the use of both Arabic and Indonesian as languages of instruction in some subjects. Despite these challenges, the use of Modern Standard Arabic among teachers and students across all branches of Ibnu Hajar Islamic Institute, from the elementary level to the language preparation stage, remains consistently implemented.